Effect of Cycling Exercise at Different Pedal Cadences on Subsequent Muscle Strength - Ruas, Vinicius Daniel de Araújo [UNESP]; Figueira, Tiago Rezende [UNESP]; Denadai, Benedito Sérgio [UNESP]; Greco, Camila Coelho [UNESP] (Elsevier, 2011)
The main purpose of this study was to compare the effects of previous high-intensity aerobic exercise at 50 and 100 rev · min -1 on subsequent strength determined through maximal repetitions (RM) and countermovement jump (CMJ). Thirteen physically active males (age, 23.0 ± 3.7 years; weight, 77.1 ± 8.8 kg; height, 179.3 ± 4.0 cm; %body fat, 14.3 ± 2.9%) performed the following procedures on different days: (1) incremental test on cycle ergometer to determine the onset of blood lactate accumulation at 50 and 100 rev · min -1; (2) three sets of RMs with the load corresponding to 10 RM in leg press 45° (LC); (3) three sets of 10 maximal CMJ in contact plate (JC); (4) four trials of 30 minutes at the onset of blood lactate accumulation obtained at 50 and 100 rev · min -1, followed by three sets of RMs with 10 RM load (L50 and L100, respectively) or three sets of maximal CMJ (J50 and J100, respectively). Strength was compromised at 100 rev · min -1 (L100 = 22.6 ± 6.0 vs. LC = 30.4 ± 1.5 repetitions) in leg press, while CMJ height was reduced at 50 rev-min -1 (J50 = 29.2 ±3.0 vs. JC = 31.7 ± 2.9 cm). The reduction in number of repetitions at L100 (26%) was significantly higher than CMJ height at J50 (8%). In conclusion, the extent of strength loss after high-intensity aerobic exercise can be dependent on both pedal cadence and strength test conditions. When aerobic cycling exercise precedes strength training, it may be beneficial to use low pedal cadences to minimize strength loss. © 2011 Chinese Taipei Society of Ultrasound in Medicine & Elsevier.
Keywords: Endurance exercise; Jump; Leg press